2016
DOI: 10.4236/ojepi.2016.64021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Spinal Metastasis in Neurosurgical Procedures: A Descriptive Study

Abstract: Objective: This study sought to identify the prevalence of operations for spinal epidural neoplastic metastases relative to other spine and neurosurgical operative procedures. Methods: This study was descriptive and involved a retrospective review of data collected from patients who underwent neurosurgeries between February 1997 and January 2015 at a single quaternary hospital. The examined population was distributed across five descriptive categories to perform numerical distributions among neurosurgical oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The three studies eligible for analysis identified internal validity integrity and homogeneity in sample datasets in accordance to the number of patients in each spinal neoplasm prevalence group (11,(14)(15) . Oxford CEBM level of evidence-based medicine criteria analyses (13) classified clinical appraisal quality as level 4 in the cross-sectional study (11) and level 3 in the two case-series studies (14)(15) . Randomized controlled trials were absent in this literature search.…”
Section: Systematic Literature Review Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The three studies eligible for analysis identified internal validity integrity and homogeneity in sample datasets in accordance to the number of patients in each spinal neoplasm prevalence group (11,(14)(15) . Oxford CEBM level of evidence-based medicine criteria analyses (13) classified clinical appraisal quality as level 4 in the cross-sectional study (11) and level 3 in the two case-series studies (14)(15) . Randomized controlled trials were absent in this literature search.…”
Section: Systematic Literature Review Resultsmentioning
confidence: 99%
“…This secondary outcome indicated that spinal intradural neoplasms were prevalent when compared with spinal metastases, the latter the most common histologic tumor type group. Comparisons in spinal neoplasms census concerning the systematic literature review indicated that 191 (22.05%) patients were operated for spinal metastases, 83 (9.59%) for epidural primary neoplasms and 592 (68.36%) for intradural neoplasms, in regard to the 3 reports cohorts of 866 (100%) patients operated for spinal and spinal tissue neoplasms (11,(14)(15) .…”
Section: Systematic Literature Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations